Antibacterial Activity of Kaempferia Galanga L. Hard Candy Against Streptococcus pyogenes and Staphylococcus aureus Bacteria Growth - Maria Belgis; Ahmad Nafi’; Giyarto Giyarto; Afina Desi Wulandari (International Journal on Food, Agriculture and Natural Resources, 2021)
Aromatic ginger (Kaempferia Galanga L.) is a spice plant that has a high volatile content with active compounds of ethyl p-methoxy cinnamate (23.65%) and ethyl cinnamate (5.98%). These two compounds have been reported to have antibacterial activity against Streptococcus pyogenes and Staphylococcus aureus, which are two types of bacteria that can cause sore throat. The application of aromatic ginger essential oil on hard candy can potentially reduce inflammation in the throat. This study aims to determine the effect of aromatic ginger essential oil concentration on hard candy in inhibiting the growth of Streptococcus pyogenes and Staphylococcus aureus bacteria and to determine their acceptance by the panelists. This research was conducted with 6 treatments of variations in the concentration of aromatic ginger essential oil, including 0%, 0.2%, 0.4%, 0.6%, 0.8%, and 1%. The results showed that the higher the concentration of aromatic ginger essential oil on hard candy would further increase the inhibition of the growth of Streptococcus pyogenes and Staphylococcus aureus bacteria. The highest inhibitory activity and the highest panelist acceptance was 1% essential oil concentration with 3.29% moisture content, 0.12% ash content, and 7.13% reducing sugar. The use of aromatic ginger essential oil on hard candy as a flavoring and well as inhibiting the growth of strep throat-causing bacteria (Streptococcus pyogenes and Staphylococcus aureus) has the potential to be developed. Keywords: Antibacterial, hard candy, aromatic ginger, essential oil, Streptococcus pyogenes, Staphylococcus aureus